Thermal analysis, kinetic behavior, reaction modeling, and comprehensive pyrolysis index of soybean stalk pyrolysis - Agnihotri N.; Mondal M.K. (My University, 2025)
In this study, soybean stalk (SS) biomass was explored for its bioenergy generation prospective by thermal degradation. Proximate, ultimate, HHV (higher heating value), and thermogravimetric (TG) analyses were performed. For TG, three heating rates (10, 15, and 25 °C/min) in nitrogen atmosphere with temperature from room temperature to 800 °C were chosen. TG experiments affirmed that maximal devolatilization occurred between 205 and 510 °C. Four iso-conversional models (Friedman, Flynn–Wall–Ozawa (FWO), Kissinger–Akahira–Sunose (KAS), and Starink) were employed for kinetic and activation energy evaluation. Values of activation energy using these models came out to be 127.62, 124.15, 124.44, and 136.28 kJ/mol, respectively. Results of the FWO model were used for thermodynamic evaluation. Average values of change of enthalpy (∆H) and Gibbs free energy (∆G) were found to be 124.29 and 167.23 kJ/mol, respectively. The pre-exponential factor (A) values lie in the range of 105–1013 s−1. Master plots and Criado method indicated complex reaction mechanism during pyrolysis. Comprehensive pyrolysis index (CPI) affirmed that a higher heating rate is favorable for SS pyrolysis. The results of physicochemical, kinetics, thermodynamics, and pyrolysis performance index reflected high bioenergy potential of SS which emphasized that pyrolysis of SS is a pragmatic approach for affordable, sustainable, and green-clean energy production. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2023.